Left Ventricular Thrombosis: Current Perspective and Use of Direct Oral Anticoagulants - A. D. Aga; A. A. Sokolova; D. A. Napalkov (Столичная издательская компания, 2023)
Left ventricular thrombus (LVT) is a serious risk factor for systemic embolism development. Despite the evident danger of this condition, current guidelines describe management of patients with this potentially fatal complication very briefly. LVT can complicate myocardial infarction where its incidence is around 10%, as well as various forms of cardiomyopathies and novel coronavirus infection. According to clinical guidelines vitamin K antagonists (VKAs) should be used as treatment of choice for thrombus resolution. However, experts point out that this therapy lacks necessary evidential base and bears certain difficulties because of pharmacokinetic and pharmacodynamical properties of VKAs. These drawbacks are absent in direct oral anticoagulants (DOACs), the possibility of using which in LVT is being actively studied. As for now, published results of 3 randomised clinical trials have demonstrated similar safety and efficacy profiles of DOACs and VKAs. Similarly, the majority of retrospective cohort studies did not observe significant differences between two groups, where some of them have shown superiority of DOACs especially in terms of earlier thrombus resolution. Nevertheless, some studies have found DOACs ineffective and even potentially unsafe regarding systemic embolism. Existing data does not allow to form an unambiguous conclusion about the equivalence of DOACs and VKAs for LVT resolution. Large randomised clinical trials are needed to determine efficacy and safety of such treatment in these patients.